Transcriptional profile of popcorn roots under aluminum stress - Pinto, Vitor Batista (2019)
Aluminum (Al) is the third most abundant element in the earth’s crust. In acid soils, with pH values at or below 5, the phytotoxic species Al 3+ is solubilized in soil solution and becomes one of the most important abiotic stresses limiting the crops production. The phytotoxic form Al 3+ inhibits root growth altering water and nutrients absorption and consequently reducing the plant development. In some species, most of this variation is controlled by a single major gene, whereas in other the characteristic is more complex. In maize Al-resistance is considered a quantitative trait. The investigation of Al-responsive genes in maize was focused mainly in an early response, but we believe that a maintenance mechanism is activated in which several metabolic processes are working at the same time during a long term of Al-exposure. This study aimed to investigate new players involved in defense response under Al stress of two contrasting popcorn lines during 72 h under stress using high-throughput RNA sequencing. The specific objectives were: i) to track the expression profile of popcorn inbred lines under Al-stress; ii) to link the RNA-seq data into maize QTLs involved in Al tolerance; iii) to perform a single nucleotide polymorphism (SNP) analysis to detect variants with predicted deleterious substitutions. The contrasting popcorn inbred lines were maintained in control and Al-treatment conditions in a chamber growth during 72h and then the total RNA from three biological replicates, in a total of 12 samples, was extracted from roots. The RNA sequencing was performed using Illumina HiSeq 2500 platform. The cDNA libraries reads were submitted to quality control analysis with FastQC software. The genome assembly was performed with the program Bowtie2 and TopHat using the B73 (RefGenv4) genome as reference. The expression levels and to identification of differentially expressed genes (DEGs) were calculated with the program Cuffdiff. A total of 1,121 DEGs were identified in the Al-sensitive line and 2,872 DEGs in the Al-resistant line. It were shared 384 DEGs in both lines. The most significant gene ontology (GO) modules were clustered in response to a stimulus. The Al-resistant line presented genes that may play a role in an efficient oxidative system against ROS, involved in cell wall stiffening and dynamic changes of the cell wall to prevent the Al ion transport via the symplast. Also, we detected transporters belonging to families already known to perform a role in Al-detoxification and organic acid exclusion, and we proposed a class of SWEET transporters that might be involved in regulation of vacuolar sugar storage under Al-stress. In the study to explore the variation and reduce the number of Al-responsive genes, it was performed the mapping of the DEGs to the chromosomes and identified SNP variants. Reads were mapped to reference genome using BWA-MEM algorithm. The mapping files were processed using Picard software. The variants were called using FreeBayes software. The SNPs were filtered using vcftools and annotated with Variant Effect Predictor. To detect DEGs inside previously Al-tolerance QTLs identified, in silico mapping was performed by a comparison between the positions of the genes and the region flanked by markers in each chromosome. This allowed the identification of genes inside maize Al-tolerance QTLs previously reported in the literature and the detection of variants that may create a defense host mechanism against Al-toxicity. We were able to highlighted some new targets, such as SNF1-related protein kinase, histone deacetylase (HDT1), SWEET transporters, delta (12)-fatty-acid desaturase (FAD), MADS-box, AP2/EREBP, HY5-like, and pathogenesis-related (PR) proteins, that may contribute to maintaining root growth under Al-stress in popcorn.